MARKETING MIX TO PROMOTE PLANTAGO MAJOR L. PROCESSING ENTREPRENEURS - Sritanu, Somchai; Chittwattanakorn, Trakul; Watthanabut, Bussakorn (Journal of MCU Nakhondhat, 2023)
This academic article has the following objectives 1) to study the current situation and the problems that hinder the business operation of Plantago major L. processing entrepreneurs in Thailand, 2) to present general knowledge, problem conditions, and properties of Plantago major L., and 3) to present the Marketing Mix that promotes the business of Plantago major L. processing entrepreneurs in Thailand. The findings of this study were derived from relevant documents and research by summarizing and interpreting the related documents and research, which are as follows: 1. Most of the entrepreneurs are single operators and small community enterprises groups. They have gotten problems with the Marketing Mix such as Product, Price, Place, and Promotion. In terms of the Products, the problems were encountered at a high level in the non-certification of standards in the production process and products by government agencies that regulate rules and regulations., 2. Plantago major L. is a well-known herb and has a long history of being used in healing and treatment. It can be used both externally and internally. Many journal papers and researches both domestically and internationally support the usefulness of Plantago major L. 3. The Marketing Mix has a significant relationship with business promotion to the Plantago major L. processing entrepreneurs in Thailand. The properties of Plantago major L. gives a positive effect on the treatment of musculoskeletal pain. Users of such products are accepted. Therefore, production should be improved in order to obtain more quality products.